Application of Image Analysis Technique in Coagulation of Milk for Paneer Manufacturing: Image Analysis in Milk coagulation - Nagaratna; Barnwal, Pradyuman; P N Raju; Hima John; Priyanka (Indian Journal of Dairy Science, 2024)
This study was aimed to investigate the coagulation process of Paneer manufacturing and to determine the optimal conditions for its production using image analysis techniques. Paneer, a traditional coagulated dairy product, is widely recognized and valued for their nutrition and easy to use. The whey images were captured and analyzed at different levels of agitator speed (20, 30 and 40 rpm) and coagulation temperatures (70, 75 and 80℃), and the L*, a*, and b* values of each sample were evaluated using Adobe Photoshop software. The a* value was specifically used to assess the greenish colour of the sample image, which is an important indicator of complete coagulation of milk. The results revealed that the optimal coagulation conditions were 70℃ coagulation temperature, 40 rpm agitator speed and 140 s coagulation time with a* value of -5.39. These findings suggest that image processing may be an effective tool for monitoring and standardizing the coagulation process of milk for Paneer manufacturing. By using this technique, the quality and consistency of Paneer may be improved, and human intervention in the production process may also be minimized.